2019
DOI: 10.4238/gmr18377
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Bioprospecting and enzymatic potential of filamentous fungi from the Bela Vista Biological Refuge in Itaipu, Brazil

Abstract: Disordered anthropic action causes relevant impacts on different ecosystems. This may endanger key species and the compounds they produce, which have potential for commercial development. We collected environmental samples from the Bela Vista Biological Refuge, belonging to ITAIPU/Brazil, over a period of three years. A total of 181 fungal species were isolated and evaluated for cellulases and xylanases, 74% of which were classified as good enzymatic producers, with a production of up to 50 U/mL of xylanase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Oumer and Abate (2018) screened pectinase-producing microorganisms from coffee pulp and observed that 13.68% of the isolates are fungi, indicating that these microorganisms are major enzyme producers. Furthermore, Corrêa et al (2019) isolated and evaluated a total of 181 fungal species for cellulases and xylanases production and described 74% were classified as good enzymatic producers. According to Sarsaiya et al (2018), the fungi Trichoderma viride, A. niger, A. fumigatus and Fusarium oxysporum have a high production capacity for the cellulase enzyme, but the fungi T. viride and A. niger are the ones that have the greatest potential for enzymatic activity of cellulose.…”
Section: Resultsmentioning
confidence: 99%
“…Oumer and Abate (2018) screened pectinase-producing microorganisms from coffee pulp and observed that 13.68% of the isolates are fungi, indicating that these microorganisms are major enzyme producers. Furthermore, Corrêa et al (2019) isolated and evaluated a total of 181 fungal species for cellulases and xylanases production and described 74% were classified as good enzymatic producers. According to Sarsaiya et al (2018), the fungi Trichoderma viride, A. niger, A. fumigatus and Fusarium oxysporum have a high production capacity for the cellulase enzyme, but the fungi T. viride and A. niger are the ones that have the greatest potential for enzymatic activity of cellulose.…”
Section: Resultsmentioning
confidence: 99%
“…The collection and isolation of the microorganism was authorized by Itaipu Binational, and the microorganism was identified by morphological analysis at the Federal University of Pernambuco. Extraction of genomic DNA, amplification of rDNA ITS1 and 4 regions to molecular identification of fungal isolate OI-1R-T was carried out as described by Corrêa et al (2019). Preservation and sporulation of the strain were performed on solid potato dextrose agar nutrient (PDA) containing 1.5% glucose (w/v), 2% agar (w/v) and 20% potato broth.…”
Section: Culture and Strainmentioning
confidence: 99%